Nanomedicine-Based Strategies for Diabetes: Diagnostics, Monitoring, and Treatment. (June 2020) - Lemmerman, Luke R.; Das, Devleena; Higuita-Castro, Natalia; Mirmira, Raghavendra G.; Gallego-Perez, Daniel
Abstract : Traditional methods for diabetes management require constant and tedious glucose monitoring (GM) and insulin injections, impacting quality of life. The global diabetic population is expected to increase to 439 million, with approximately US$490 billion in healthcare expenditures by 2030, imposing a significant burden on healthcare systems worldwide. Recent advances in nanotechnology have emerged as promising alternative strategies for the management of diabetes. For example, implantable nanosensors are being developed for continuous GM, new nanoparticle (NP)-based imaging approaches that quantify subtle changes in β cell mass can facilitate early diagnosis, and nanotechnology-based insulin delivery methods are being explored as novel therapies. Here, we provide a holistic summary of this rapidly advancing field compiling all aspects pertaining to the management of diabetes. Highlights: Following success in other medical areas, nanotechnology is currently generating immense promise for alternative strategies for diabetes management. Magnetic nanoparticle-based imaging of β cell mass and immune cell activity, as well as quantum dot (QD)-enabled gas sensors, offer potential new avenues for early detection. Multiwalled-carbon nanotubes, graphene nanocomposites and QDs provide discrete sensors with improved sensitivity and efficiency for glucose and insulin monitoring. Cell therapies supported by nanofiber-based scaffolds or immunoisolation membranes, and glucose-responsive nanogels and nanovesicles offer novel approaches to controlled insulin release.